Phytochemical composition and bioactivity of Parkia timoriana leaf extract from Kediri, Indonesia in various solvent polarities - ATMIRA SARIWATI; FITA SARI; VENTY SURYANTI; DESI SUCI HANDAYANI; HILDA ALFIYANI SETYONO; NINIS YULIATI (Society for Indonesian Biodiversity, 2024)
Abstract. Sariwati A, Sari F, Suryanti V, Handayani DS, Setyono HA, Yuliati N. 2024. Phytochemical composition and bioactivity of Parkia timoriana leaf extract from Kediri, Indonesia in various solvent polarities. Biodiversitas 25: 4900-4908. The potential therapeutic uses of bioactive chemicals found in natural sources have led to a significant increase in focus on their investigation in recent years. Parkia timoriana (DC.) Merr. has secondary metabolites, which have been used as a traditional medicine. This work studies the phytochemical composition and bioactivities evaluation of the P. timoriana leaf extract of varying solvent polarities, such as methanol, water, ethyl acetate, and hexane. The methanol extract has the highest secondary metabolite contents, excluding terpenoids contents. The Follin-Ciocalteu method showed that the total phenolic content of methanol extract was 302.02 mg GAE/g. The aluminum chloride colorimetric method revealed that the total flavonoid content of the methanol extract was 256.85 mg QE/g. The tannin acid, alkaloids, saponins, and terpenoids contents of methanol extracts were determined by Spectrophotometer UV-Vis, which were found to be 32.07 mg TAE/g, 23.86 mg CoE/g, 18.35 mg DE/g, 5.23 mg Linalool Eq./g, and respectively. The highest terpenoid contents were found in hexane extract, which was 11.34 mg of Linalool Eq./g. Antioxidant activities of the extracts were assessed by measuring the free-radical of 2, 2-diphenyl-1-picrylhydrazyl (DPPH) and scavenge of 2,2'-azinobis (3-ethylbenzene-thiazoline-6-sulfonic-acid (ABTS)). The methanol extract was shown to have the strongest antioxidant activity, where the DPPH and ABTS IC50 values were 47.78 and 39.54 µg/mL, respectively. The methanol extract exhibited the greatest antimicrobial activities, where the inhibition zone for Candida albicans and Escherichia coli fungus were 21 and 22 mm, respectively. Antidiabetic effects were assessed in vitro by blocking ?-amylase and ?-glucoside. The methanol extract shows an inhibition of 50.19 µg/mL for ?-glucoside and 42.50 µg/mL for ?-amylase. The secondary metabolites of P. timoriana leaf are great building blocks for making potent medications.